Spotlight on sirukumab for the treatment of rheumatoid arthritis: the evidence to date - Lazzerini, Pietro Enea (Drug Des Devel Ther, 2016)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease primarily affecting synovial joints and is characterized by persistent high-grade systemic inflammation. Proinflammatory cytokines, particularly interleukin-6 (IL-6), are of crucial importance in the pathogenesis of the disease, driving both joint inflammation and extra-articular comorbidities. Tocilizumab, a humanized IL-6 receptor-inhibiting monoclonal antibody, has been the first, and, to date, the only, IL-6 inhibitor approved for the treatment of RA. Many studies have demonstrated the potency and effectiveness of tocilizumab in controlling disease activity and radiological progression of RA. These successful results have encouraged the development of novel IL-6 inhibitors, among which a promising agent is sirukumab (SRK), a human anti-IL-6 monoclonal antibody currently under evaluation in Phase II/III studies in patients with RA, systemic lupus erythematosus, giant-cell arteritis, and major depressive disorder. The evidence to date indicates SRK as an effective and well-tolerated new therapeutic tool for patients with active RA, with some preliminary data suggesting a specific beneficial impact on relevant systemic complications associated with the disease, such as depression and cardiovascular disease. Conversely, although pathophysiological considerations make plausible the hypothesis that IL-6 blockade with SRK may also be beneficial in the treatment of many diseases other than RA (either autoimmune or not), available clinical data in patients with systemic lupus erythematosus do not seem to support this view, also giving rise to potentially relevant concerns about drug safety. If large Phase III clinical trials currently in progress in patients with RA confirm the efficacy and tolerability of SRK, then in the long term, this drug could, in the near future, occupy a place in the treatment of the disease, potentially also opening the doors to a more extended use of SRK in a wide range of disorders in which IL-6 plays a key pathogenic role.